Increased absorption and use of nutrients induced by Si is an indicator for tolerance to water deficit in a common bean cultivar cultivated in the field with and without application of K - Teixeira, Gelza Carliane Marques [UNESP]; Gonzalez-Porras, Carlos Vital [UNESP]; Messias Ferreira, Patrícia [UNESP]; Prado, Renato De Mello [UNESP]; Silva Oliveira, Kamilla [UNESP]; Carvalho, Lívia Tálita da Silva [UNESP]; Palaretti, Luiz Fabiano [UNESP] (Frontiers, 2024)
Introduction: Reduced water content in the soil triggers physiological, biochemical, and morphological damage to plants, aggravated by nutritional deficiency. One possible strategy to mitigate this damage comprises the use of silicon (Si). This study investigated whether Si can mitigate the damage caused by water deficit through nutritional mechanisms in bean plants grown under field conditions. Furthermore, it investigated whether the effectiveness of Si is influenced by water availability in the soil and the Si dose supplied. Methods: Therefore, two split-plot experiments were carried out: with and without K supply. In both experiments,the treatments comprised a 3 × 4 factorial scheme. Treatments included three water regimes: 80% (no water deficit), 60% (moderate water deficit), and 40% (severe water deficit) of the soil’s water retention capacity. Moreover, they comprised four doses of Si supplied via fertigation—0 kg/ha, 4 kg/ha, 8 kg/ha, and 12 kg/ha—arranged in a randomized block design with four replications. Results and discussion: The appropriate dose of Si to be applied increased with the severity of the water deficit, with the recommended dose being 6 kg/ha, 7 kg/ha, and 8 kg/ha of Si for adequate water conditions, moderate water deficit, and severe water deficit, respectively.
Keywords: beneficial element; nutritional efficiency; plant nutrition; water deficiency; water effciency